2010
DOI: 10.1111/j.1365-263x.2010.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in 12‐ to 17‐year‐old athletes participating in the German Special Olympics

Abstract: Adolescents with intellectual disabilities seem to have benefited from various caries preventive measures which had been introduced during the last two decades in Germany but still have a poorer oral health than the general population. More specific prevention programmes seeking close cooperation with parents, custodians, and caretakers should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 24 publications
1
35
0
13
Order By: Relevance
“…Through the quality assessment (Table ), the score ranged from 4 to 7 out of 10 possible points. Of the 16 studies that underwent a risk of bias assessment, eight (50%) were considered to have a moderate risk of bias and eight (50%) were considered to have a high risk of bias …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the quality assessment (Table ), the score ranged from 4 to 7 out of 10 possible points. Of the 16 studies that underwent a risk of bias assessment, eight (50%) were considered to have a moderate risk of bias and eight (50%) were considered to have a high risk of bias …”
Section: Resultsmentioning
confidence: 99%
“…A population sample of 35,732 individuals was enrolled in this review, ranging from 160 to 14,319 athletes. Thirteen articles were cross‐sectional studies, another study was a retrospective, one study did not report the design, and Feldman et al . was a pilot study.…”
Section: Resultsmentioning
confidence: 99%
“…The studies regarding oral health status of child athletes mainly focus on children with intellectual disabilities [29][30][31][32]. Thriandini et al [29] screened child athletes with a mean age of 13.4 and observed that almost 70% of the athletes had visible untreated caries.…”
Section: Discussionmentioning
confidence: 99%
“…Oredugba et al [30) conducted a similar study in Nigeria and reported that 22.4% of the child athletes had untreated caries lesions. Bissar et al [31) evaluated child athletes between 12-17 years in the Special Olympics in Germany and observed a caries prevalence of 58% and a mean DMFT of 2.3. In a study where Puerto Rican athletes were included [32], it was reported that almost 45% of the athletes had untreated dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Als Kariesrisikopatienten dürften aber gerade Kinder und Jugendliche mit Behinderungen bezüglich ihrer Mundgesundheit von der evidenzbasierten kariespräventiven Maßnahme der FV profi tieren[ 29 ] . So zeigten Bissar et al[ 23 ] , dass die FV bei Kindern und Jugendlichen mit geistiger Behinderung den Kariesbefall deutlich reduziert. Übereinstimmend zum Schrifttum wiesen Erfurter SchGB im Vergleich zu denjenigen mit anderen Behinderungen eine schlechtere Parodontalgesundheit auf…”
unclassified